SALES SYSTEM DRUGS ON PHARMACIES HUSADA USING MICROSOFT VISUAL BASIC 6.0 - Supeni Siskawati; Ire Puspa Wardhani, Skom, MMSi Ire Puspa Wardhani, Skom, MMSi (Jurnal Sistem Informasi, 2006)
Valuable information is the information quickly and accurately. So in need of acomputerized system as a means of support. Sales System Drugs On PharmaciesHUSADA designed with the goal to get the information quickly and accurately aswell as secure data storage. So with the end result is useful for decision making.